2017
DOI: 10.1371/journal.pone.0170591
|View full text |Cite|
|
Sign up to set email alerts
|

Toyocamycin attenuates free fatty acid-induced hepatic steatosis and apoptosis in cultured hepatocytes and ameliorates nonalcoholic fatty liver disease in mice

Abstract: Background and aimsA high serum level of saturated free fatty acids (FFAs) is associated with the development of nonalcoholic fatty liver disease (NAFLD). X-box binding protein-1 (XBP-1) is activated by FFA treatment upon splicing. XBP-1 is a transcription factor induced by the endoplasmic reticulum (ER) stress sensor endoribonuclease inositol-requiring enzyme 1 alpha (IRE1α). However, the role of XBP-1 in NAFLD remains relatively unexplored. Toyocamycin was recently reported to attenuate the activation of XBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…In addition, endoplasmic reticulum (ER) stress and mitochondrial dysfunction ultimately lead to apoptosis of hepatic cells, which is known as NASH [ 26 ]. As shown in our results, treatment with 300 μ M PA caused prominent apoptotic death of HepG2 cells, as had already been reported by others [ 27 ]. As expected, we found that ACE had statistically significant anti-NASH effects ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, endoplasmic reticulum (ER) stress and mitochondrial dysfunction ultimately lead to apoptosis of hepatic cells, which is known as NASH [ 26 ]. As shown in our results, treatment with 300 μ M PA caused prominent apoptotic death of HepG2 cells, as had already been reported by others [ 27 ]. As expected, we found that ACE had statistically significant anti-NASH effects ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…**P < 0.01, ***P < 0.001 versus the control group; ##P < 0.01, ###P < 0.001 versus the HFD group. accumulation under the HFD and obesity conditions, leading to lipotoxic liver injury, which activates endoplasmic reticulum (ER) stress and mitochondrial dysfunction-dependent apoptotic signaling, resulting in hepatic apoptosis (29,30). In the present study, our data showed that HFD induced marked hepatic fat accumulation, augmented apoptosis-related protein levels and the percentages of hepatocytes undergoing apoptosis, indicating the occurrence of hepatic lipoapoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…With respect to the anti-tumor functions of toyocamycin, some reports noted that toyocamycin inhibited XBP1 splicing via a conformational change in IRE1α to attenuate the activation of XBP1 [ 20 , 45 ]. One study reported that toyocamycin did not cause IRE1α phosphorylation, but specifically blocked its endoribonuclease activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%